Implementation of Reportage-based Speaking Skills Learning in Vocational High Schools - Nugroho, Setyo Eko Wahyu Addin; Rahmawati, Laili Etika; Huda, Miftakhul (Jurnal Pendidikan Indonesia, 2023)
Learning Indonesian speaking skills in news texts with a reporting strategy as a role model is implemented to solve the problem of students' lack of speaking and presenting skills. The purpose of this study was conducted to analyze the implementation of the reportage-based speaking skill learning method in SMK. The type of approach to this research is descriptive qualitative, as a research method based on postpositivism philosophy with objects of natural conditions (the opposite of this research is experimentation). The research was conducted by interviewing, observing, and taking notes for data collection. Research subjects are researchers and their partners. Data analysis activities are carried out by explaining the technique of planning, implementing, and evaluating learning as a strategy for learning speaking skills. The findings in this study showed that students experienced an increase in their speaking skills and demonstrated in public schools with a score of 71 out of 21 instrument indicators regarding the method of applying reportage-based students' speaking skills in Vocational High Schools. In this study, the average recapitulation results were obtained at 3.38 with a maximum value of 4. The value calculation was carried out using the formula in the evaluation process.